Pengaruh Pelayanan dan Produk Tabungan Bagi Hasil Terhadap Keputusan Menabung Pada BSI KC Kartasura - Rudiatna, Talitha Dwi; Arfiansyah, Mufti Arief (Journal of Economics and Business Research (JUEBIR), 2023)
Customer experience can have an impact on decisions taken by consumers when using services in the banking sector. One of the impacts can be the quality of service and product sharing. This analysis is useful for knowing the influence of service quality and profit-sharing savings products on customers' decisions to save at Bank Syariah Indonesia Kartasura branch office. This research uses a questionnaire survey method approach to obtain data from 210 respondents to BSI savings customers by distributing questionnaires on a Likert scale. Analysis techniques use Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Multicollinearity Test, Multiple Regression Analysis Test (t, F Test, and Coefficient of Determination). The research results show that service quality can have a positive influence on customers' savings decisions at Bank Syariah Indonesia Kartasura Branch Office. Profit sharing savings products also have a very significant influence on customers' savings decisions at Bank Syariah Indonesia Kartasura Branch Office